A systematic review on the factors affecting effective communication between registered nurses and oncology adult patients in the inpatient setting - Tay, L.; Hegney, Desley; Ang, E. (University of Adelaide, 2010)
Background: Effective nurse-patient communication is essential in the development of therapeutic relationships and meeting the cognitive and affective needs of oncology patients. However, the emotional load in cancer nursing has made communication additionally challenging. Objective: This review aimed to establish the best available evidence regarding the factors affecting effective communication between registered nurses and adult oncology patients in inpatient setting. Inclusion criteria: Types of participants - This review considered studies that included registered nurses and inpatient oncology adults who were more than 21 years of age. This review considered studies carried out in inpatient settings, regardless of ward specialty, whilst active or palliative cancer treatments were administered. Phenomena of interest - This review considered the factors affecting effective communication between registered nurses and inpatient oncology adults. Types of studies - This review considered both quantitative (randomized controlled trials, non-randomized controlled trials, before and after studies, cohort observational, descriptive survey and mixed method studies) and qualitative (including, but not limited to, phenomenology, grounded theory and ethnography) research studies on the factors affecting effective communication between registered nurses and inpatient oncology adults.Search strategy: The search strategy aimed to find studies published in English language and not limited by year of publication. A three-step search strategy was utilized in each component of this review. The grey literature was not included in this review. Data extraction - Quantitative data were extracted using standardized data extraction tools adapted from the Joanna Briggs Institute-Meta Analysis of Statistics Assessment and Review Instrument (JBI-MAStARI). Qualitative data were extracted using the standardized data extraction tool from the Joanna Briggs Institute-Qualitative Assessment and Review Instrument (JBI-QARI). Data analysis - Quantitative data were presented in a narrative summary. Qualitative findings were categorised using JBI-QARI tool to generate synthesised findings.Results: One quantitative, two mixed method and four qualitative studies were included in this review. Combined findings of the narrative summary and meta-synthesis identified promoting and inhibiting factors in the characteristics of nurses, patients, and the environment. Promoting factors in nurses included genuineness, competency and supportive facilitation skills. However, the role of post-basic training in improving communication remained inconsistent. In patients, active participation in their own care and information-seeking behaviour promoted nurse-patient communication. Conversely, inhibiting factors in nurses included task orientation, fear of own death and low self-awareness of own verbal behaviours. Nurses also communicated less effectively during psychological assessments and emotionally-charged situations. For patients, their unwillingness to discuss the disease/feelings, their preference to seek emotional support from family and friends and the use of implicit cues inhibited effective communication. Environmentally, a supportive ward environment increased the use of facilitative behaviour in nurses, whereas the existence of conflict among staff increased the use of blocking behaviours. Cultural norms in the Chinese society also inhibited nurse-patient communication. Conclusion: Within the constraints of the study and the few quality papers available, it appears that personal characteristics of patients and nurses are the key influencing factors of effective nurse-patient communication in the oncology setting. Very little evidence exists on the role of environment in effective nurse-patient communication, particularly within an Asian setting.Implications for practice: Using evidence from the quantitative component of the review, nurses need to focus on the mental health status of patients admitted with a recurrence of cancer. Education programs can be implemented to inform nurses about the challenges in communication and develop strategies to counter these obstacles. Using evidence from the qualitative component of the review, nurses should build rapport and encourage active patient participation in their care in order to enhance patient disclosure. Nurses should also be mindful of patients‟ psychological readiness to communicate and respect their preference as to whom they wish to share their thoughts/emotions with. Institutions need to design ward structures (ward culture and nurses‟ workload) that support and/or encourage nurses to be person-oriented and take responsibility for providing holistic care to patients. Both the quantitative and qualitative components of the review indicated the need to improve nurses‟ communication skills and their receptivity to patient cues. Implications for research: An explorative descriptive study on the effect of the Asian culture on the effective communication in the oncology setting is required to add to the small amount of knowledge in this area. Descriptive or mixed method studies to ascertain the effect of the patient‟s age and place within the oncology treatment cycle are also warranted. The lack of evidence on the effectiveness of post-basic communication courses would be best gathered by a descriptive study, followed by a before-and-after randomised controlled trial to test different education programs.